Red and blue language: Word choices in the Trump and Harris 2024 presidential debate - Philipp Wicke; Marianna M. Bolognesi (PLoS ONE, 2025)
Political debates are a peculiar type of political discourse, in which candidates directly confront one another, addressing not only the the moderator’s questions, but also their opponent’s statements, as well as the concerns of voters from both parties and undecided voters. Therefore, language is adjusted to meet specific expectations and achieve persuasion. We analyse how the language of Trump and Harris during the Presidential debate (September 10th, 2024) differs in relation to semantic and pragmatic features, for which we formulated targeted hypotheses: framing values and ideology, appealing to emotion, using words with different degrees of concreteness and specificity, addressing others through singular or plural pronouns. Our findings include: differences in the use of figurative frames (Harris often framing issues around recovery and empowerment, Trump often focused on crisis and decline); similar use of emotional language, with Trump showing a slightly higher tendency toward negativity and toward less subjective language compared to Harris; no significant difference in the specificity of candidates’ responses; similar use of abstract language, with Trump showing more variability than Harris, depending on the subject discussed; differences in addressing the opponent, with Trump not mentioning Harris by name, while Harris referring to Trump frequently; different uses of pronouns, with Harris using both singular and plural pronouns equally, while Trump using more singular pronouns. The results are discussed in relation to previous literature on Red and Blue language, which refers to distinct linguistic patterns associated with Republican (Red) and Democratic (Blue) political ideologies.